ACUTE MYOCARDITIS WITH CARDIOGENIC SHOCK AND MULTIPLE ORGAN FAILURE, FOLLOWED BY BILATERAL PANUVEITIS MASQUERADING AS ENDOGENOUS ENDOPHTHALMITIS, DUE TO TOXOPLASMA GONDII IN AN IMMUNOCOMPETENT PATIENT. Issue Volume 15:Issues 5(2021) (September 2021) - Filipowicz, Artur; Coca, Mircea N.; Blair, Barbra M.; Chang, Peter Y.
Abstract : Purpose: To report a case of systemic and ocular toxoplasmosis in an immunocompetent patient, who developed myocarditis with resulting cardiogenic shock and multiple organ failure, followed by bilateral panuveitis masquerading as endogenous endophthalmitis. Methods: Single case report with images. Results: A 59-year-old man with a history of monoclonal gammopathy of undetermined significance and associated scleromyxedema but otherwise immunocompetent was admitted to the intensive care unit for cardiogenic shock and multiple organ failure due to presumed viral myocarditis. After hospital discharge, ophthalmic examination revealed what seemed to be endogenous fungal endophthalmitis in both eyes. The ocular inflammation failed to improve on local and systemic antifungal therapies. After repeated testing and vitrectomy, the causative organism responsible for his intraocular inflammation remained elusive. The patient was then found to have significantly elevated serum titers of anti– Toxoplasma gondii IgG and IgM, followed by an appearance of a focal retinochoroidal lesion more typical of ocular toxoplasmosis. Systemic anti- Toxoplasma therapy led to resolution of intraocular inflammation, and the patient had since fully recovered from the myocarditis and its multiple comorbidities. Of note, myocardial biopsy and polymerase chain reaction testing of aqueous and vitreous fluids were all negative for Toxoplasma . Conclusion: Even in an immunocompetent patient, Toxoplasma can result in myocarditis with significant morbidities and even death, and its ocular manifestation may be quite different from the classic focal retinochoroiditis. In addition, polymerase chain reaction analysis of ocular fluids can be unreliable in an immunocompetent host, and thus treatment decision should be guided by clinical history and examination findings. Abstract : We report a case of toxoplasmosis in an immunocompetent patient, who developed myocarditis resulting in cardiogenic shock and multiple organ failure, followed by bilateral panuveitis that masqueraded as endogenous endophthalmitis.